Transcriptomic analysis provides insight into the regulation mechanism of silver ions (Ag+) and jasmonic acid methyl ester (MeJA) on secondary metabolism in the hairy roots of Salvia miltiorrhiza Bunge (Lamiaceae) - Ying Cheng; Xinyu Hong; Lan Zhang; Wan Yang; Youran Zeng; Zhuoni Hou; Zongqi Yang; Dongfeng Yang (Medicinal Plant Biology, 2023)
Salvia miltiorrhiza Bunge (Lamiaceae) is a traditional medicinal plant. Its main active components are tanshinones and salvianolic acid B (SAB). Abiotic elicitors such as silver ions (Ag+) and jasmonic acid methyl ester (MeJA) are reported to promote the accumulation of secondary metabolites in the hairy roots of S. miltiorrhiza. However, the mechanisms underlying the working of the elicitors remains unclear. For this reason, transcriptome quantitative analysis was conducted to describe the overall expression of elicitors-treated hairy roots, and key protein-encoding genes were identified in the MVA pathway which had a positive effect on tanshinone accumulation. Upstream genes in the biosynthetic pathway of SAB were more responsive to MeJA. Transcription factors (SmWRKY73, SmbHLH25), genes in the GA signaling pathway (SmGA2ox, SmGA3ox) and ABA signaling pathway (SmNCED, SmCYP707A) may be involved in regulating tanshinone and SAB biosynthesis. Upregulated transcription factors were highly correlated in response to Ag+ treatment and MeJA treatment, and Ag+ treatment had a better induction effect on transcription factors than MeJA treatment. Gene cluster mining and co-expression network construction further revealed the contribution of gene clusters to tanshinone biosynthesis, and Sm2OGD was likely involved in tanshinone biosynthesis. In conclusion, the current study screened the key genes for transcription factors and hormone signaling pathways that may promote the accumulation of tanshinones and SAB. The results improved the regulatory network of Ag+ and MeJA-mediated secondary metabolite biosynthesis in S. miltiorrhiza hairy roots, and improved our insight into the regulatory mechanisms involved in the biosynthesis of tanshinones and SAB.